2018
DOI: 10.1002/acm2.12429
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam CT for QA of synthetic CT in MRI only for prostate patients

Abstract: PurposeMagnetic resonance imaging (MRI)‐only radiotherapy is performed without computed tomography (CT). A synthetic CT (sCT) is used for treatment planning. The aim of this study was to develop a clinically feasible quality assurance (QA) procedure for sCT using the kV‐cone beam CT (CBCT), in an MRI‐only workflow for prostate cancer patients.Material and methodThree criteria were addressed; stability in Hounsfield Units (HUs), deviations in HUs between the CT and CBCT, and validation of the QA procedure. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Even though sCT dosecalculation has been widely investigated, there still seems to be a need for QA to detect large dosimetric errors. In clinical routine, the sCT error detection could be performed directly after the first fraction using CBCT [34].…”
Section: Discussionmentioning
confidence: 99%
“…Even though sCT dosecalculation has been widely investigated, there still seems to be a need for QA to detect large dosimetric errors. In clinical routine, the sCT error detection could be performed directly after the first fraction using CBCT [34].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic review identified 6 articles investigating MR-only commissioning processes. 15,21,[35][36][37][38] A key summary of study results can be found in Table 5.…”
Section: Mr-only Commissioning Processesmentioning
confidence: 99%
“…Palmer et al 38 developed and validated a quality assurance procedure for assessing synthetic CT clinical feasibility using kV-CBCT, where CBCT scans were used to recalculate the synthetic CT treatment plan as a check of its dose calculation accuracy.…”
Section: Mr-only Commissioning Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of magnetic resonance imaging (MRI) for radiation therapy simulations has gained popularity because it provides superior soft tissue contrast compared with conventional computed tomography (CT), potentially allowing more accurate target delineation without exposing the patient to unnecessary ionizing radiation. Co‐registration of two image sets using deformable image registration (DIR) before and during treatment is used to create a foundation for delineating targets to judge the need for adaptive radiation therapy. However, DIR errors in commercial software used with MRI have not been widely reported.…”
Section: Introductionmentioning
confidence: 99%